Design and tests of the new partially ionized beam source - Koh, SK; Jang, HG; Choi, WK; Jung, HJ; Kondranine, SG; Kralkina, EA (AMER INST PHYSICS, 1996)
We developed and evaluated a new partially ionized beam (PIB) source to deposit high quality Cu films. The novelty of the PIB source lies in the fact that the crucible and ionization parts are spaced in one cylindrical shell to make its structure compact and to get a uniform beam profile, but their electric circuits are not separated. In this article, we report the characteristics of the PIB source, such as voltage-ampere characteristics of the crucible and ionization parts, Cu+ ion beam uniformity with a change of the ionization currents, and deposition rate. (C) 1996 American Institute of Physics.
Keywords: CLUSTER BEAM; FILMS; DEPOSITION; GROWTH